L4 and L5 Spondylectomy for En Bloc Resection of Giant Cell Tumor and Review of the Literature - Santiago-Dieppa, David R.; Hwang, Lee S.; Bydon, Ali; Gokaslan, Ziya L.; McCarthy, Edward F.; Witham, Timothy F. (Evidence-Based Spine-Care Journal, 2014)
Study Design Case report and review of the literature.Objective We present the case of a two-level lumbar spondylectomy at L4 and L5 for en bloc resection of a giant cell tumor (GCT) and lumbopelvic reconstruction.Methods A 58-year-old woman presented with a 7-month history of progressive intractable back and leg pain secondary to a biopsy-proven Enneking stage III GCT of the L4 and L5 vertebrae. The patient underwent a successful L4–L5 spondylectomy and lumbopelvic reconstruction using a combined posterior and anterior approach over two operative stages.Results Postoperative complications included a deep wound infection and a cerebrospinal fluid leak; however, following surgical debridement and long-term antibiotic treatment, the patient was neurologically intact with minimal pain and there was no evidence of tumor recurrence or instrumentation failure at more than 2 years of follow-up.Conclusion Spondylectomy that achieves en bloc resection is a viable and effective treatment option that can be curative for Enneking stage III GCTs involving the lower lumbar spine. The lumbosacral junction represents a challenging anatomic location for spinal reconstruction after spondylectomy with unique technical considerations.
Keywords: giant cell tumor; osteoclastoma; spondylectomy; lumbar spine; lumbopelvic reconstruction